2008
DOI: 10.1128/cvi.00336-07
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-Specific and Age-Dependent Generation of Pneumococcal Polysaccharide-Specific Memory B-Cell and Antibody Responses to Immunization with a Pneumococcal Conjugate Vaccine

Abstract: Glycoconjugate vaccines have dramatically reduced the incidence of encapsulated bacterial diseases in toddlers under 2 years of age, but vaccine-induced antibody levels in this age group wane rapidly. We immunized adults and 12-month-old toddlers with heptavalent pneumococcal conjugate vaccine to determine differences in B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 83 publications
(85 reference statements)
4
47
0
Order By: Relevance
“…A greater frequency of PCs is generated following the third dose of MenCCV than following the first, 8 although in toddlers receiving their first dose of pneumococcal conjugate vaccine at 12 mo of age, revaccination at 14 mo did not increase PC frequency in peripheral blood relative to the same time point (1 wk post-vaccination) at 12 mo. 10 Despite showing similar kinetics, there are differences in the number of plasma cells induced by plain polysaccharide and glycoconjugate vaccines. In adolescents receiving either a booster dose of MenCCV or MenCPS, both of which contained the same quantity of polysaccharide antigen, the PC response was of greater magnitude in the glycoconjugate group, although there were no differences in the timing of responses.…”
Section: Plasma Cell Frequency Following Vaccinationmentioning
confidence: 99%
See 3 more Smart Citations
“…A greater frequency of PCs is generated following the third dose of MenCCV than following the first, 8 although in toddlers receiving their first dose of pneumococcal conjugate vaccine at 12 mo of age, revaccination at 14 mo did not increase PC frequency in peripheral blood relative to the same time point (1 wk post-vaccination) at 12 mo. 10 Despite showing similar kinetics, there are differences in the number of plasma cells induced by plain polysaccharide and glycoconjugate vaccines. In adolescents receiving either a booster dose of MenCCV or MenCPS, both of which contained the same quantity of polysaccharide antigen, the PC response was of greater magnitude in the glycoconjugate group, although there were no differences in the timing of responses.…”
Section: Plasma Cell Frequency Following Vaccinationmentioning
confidence: 99%
“…Twelve month old toddlers with little or no prior exposure to encapsulated bacteria required at least 2 doses of PCV-7 to reach B MEM frequencies equivalent to those following a single dose in adults. 10 However, all of the adults in this study already had detectable polysaccharide-specific B MEM at baseline, likely induced by prior pneumococcal colonization, in effect priming the immune system. Another study reported that age at primary vaccination (ranging between 6 mo and 34 y) with a glycoconjugate did not affect the induction and persistence of polysaccharide-specific B MEM .…”
Section: -Valent Pneumococcal Polysaccharide Vaccine (Ppv-23)mentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 PBMCs were first isolated from whole blood using lymphoprep™ (Axis-Shield Diagnostics) density gradient centrifugation. After a wash step, PBMCs were cultured at a concentration of 2 × 10 5 cells/well in a mixture of SAC (S. aureus Cowan strain, 1:5000, Calbiochem), CpG oligodeoxynucleotide 2006 (1.8 µg/mL, Source Bioscience) and pokeweed mitogen (PWM, 83 ng/ mL, Sigma) for 6 d at 37 °C, 5% CO 2 , and 95% humidity.…”
Section: Pbmc Isolation and Elispotmentioning
confidence: 99%